Identification of heredity kernels and their influence on the life time of glass/polyester composites - Olodo, Emmanuel; Adjovi, E.C.; Adanhounme, Villévo (Zielona Góra: Uniwersytet Zielonogórski)
One of the major problems encountered in prediction of hereditary viscoelastic behavior of polymeric composites is the determination of heredity kernels. This issue comes down to identification of the model characterizing the viscoelastic properties of these materials. The purpose of this work is to propose a model for prediction of viscoelastic nonlinear behavior of laminate composite with polyester matrix, through the study and analysis of heredity kernels and their influence on the life time of this material. Identification of this model required experimental determination at room temperature, of viscoelastic parameters of heredity kernels by macroscopic approach. These data provide predictive tools for establishment of the life time and long term stress limit under static complex loading for this type of material.
Keywords: heredity kernels; viscoelastic parameters; life time